Utilizing the SDGs to develop a blue economy capacity framework enabling a shift from an ocean economy to a blue economy in Canada - Noonan-Birch, Ronnie; Adams, Michelle; Ross, Marie-Chantal (Frontiers in Marine Science, 2024)
Canada has committed to establishing a socially equitable, environmentally sustainable and economically viable blue economy but has not yet determined a sustainability standard that industry must meet to be included in this aspirational blue economy. For the blue economy to be an effective, sustainable alternative to the regular ocean economy, clear criteria for ocean business must be established to reduce the risk of blue washing. The UN Sustainable Development Goals (SDGs) provide an ideal theoretical basis from which to develop a marine sector standard for blue economy industry. Using a criteria-based approach, this work selected relevant SDG targets that can guide Canada’s ocean industry in the transition to a blue economy. Through a stepwise process, the selected targets were further contextualized to the company level resulting in a blue economy capacity assessment framework (BECF) that offers four blue economy industry aims and associated enabling mechanisms. The BECF practically links the theory of the SDGs to a desired outcome, providing a method for an ocean-based company to assess its contribution to all three dimensions of Canada’s blue economy.